INSECT FORAGERS AND THEIR ROLE IN POLLINATION OF Bruguiera gymnorrhiza (L.) Savigny (Rhizophoraceae) FROM LOTHIAN WILDLIFE SANCTUARY, SUNDARBAN BIOSPHERE RESERVE - GAINE, TANUSHREE; DAS, RANJAN; MITRA, BULGANIN; CHAUDHURI, PUNARBASU (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
The purpose of this study was to identify the insect foragers and their biological association with Bruguiera gymnorrhiza, a true mangrove species from Lothian Wildlife Sanctuary (LWLS) of Sundarban Biosphere Reserve (SBR). The study was conducted in the time of flowering periods of B. gymnorrhiza during the year 2017 to 2018. Each plant individual was monitored for the time period from 7 am to 5 pm with 2 hours intervals. After obtaining the necessary data for the study, the flower visitors of the respective plants were photographed and collected by handpicking/sweeping with insect net. Only four insect species, Rhynchium haemorrhoidale haemorrhoidale, Apis mellifera, Camponotus compressus (Hymenoptera) and Micraspis discolor (Coleoptera) were observed as insect foragers of B. gymnorrhiza in LWLS of SBR. In view of time of visitation, time spent on flowers, adherence of the pollen grains to their bodies and other activities of the insect foragers within flowers, it can be said that A. mellifera and R. haemorrhoidale haemorrhoidale may play a major role in the pollination process of B. gymnorrhiza in LWLS of SBR whereas, M. discolor can be considered as merely foragers or chance pollinators of B. gymnorrhiza in LWLS.